2012
DOI: 10.1021/jp210057x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance Line Shifts and Line Shape Changes Due to Heisenberg Spin Exchange and Dipole–Dipole Interactions of Nitroxide Free Radicals in Liquids 8. Further Experimental and Theoretical Efforts to Separate the Effects of the Two Interactions

Abstract: The work in Part 6 of this series (J. Phys. Chem. A 2009, 113, 4930), addressing the task of separating the effects of Heisenberg spin exchange (HSE) and dipole-dipole (DD) interactions on EPR spectra of nitroxide spin probes in solution, is extended experimentally and theoretically. Comprehensive measurements of perdeuterated 2,2,6,6-tetramethyl-4-oxopiperidine-1-oxyl (pDT) in squalane, a viscous alkane, paying special attention to lower temperatures and lower concentrations were carried out in an attempt to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(66 citation statements)
references
References 29 publications
2
63
1
Order By: Relevance
“…12 The slopes of plots of A B vs c yield the broadening constants 14 B ′ and 15 B ′, which are shown in Figure 2a for the two isotopes; Figure 2b shows their ratios. Data for the open squares in Figure 2a were taken from Part 6.…”
Section: Resultsmentioning
confidence: 99%
“…12 The slopes of plots of A B vs c yield the broadening constants 14 B ′ and 15 B ′, which are shown in Figure 2a for the two isotopes; Figure 2b shows their ratios. Data for the open squares in Figure 2a were taken from Part 6.…”
Section: Resultsmentioning
confidence: 99%
“…The HSE and DD induced dispersion can be used for separating the effects of HSE and DD interactions on EPR spectra of nitroxide spin probes in solution. 43 Even in the absence of HSE and DD, which is when the concentration of the spin probe is extremely low, the spectral fitting of the EPR lines still reveals the existence of dispersion in the EPR line shape. This dispersion contribution previously presented in Figure 12 of ref 43 and Figures S2–S4 in the Supporting Information could be explained by the Freed et al approach 44 which is based on the stochastic Liouville equation and involves a relaxation matrix with all contributions: secular, pseudo-secular and non-secular.…”
Section: Methodsmentioning
confidence: 99%
“…43 Even in the absence of HSE and DD, which is when the concentration of the spin probe is extremely low, the spectral fitting of the EPR lines still reveals the existence of dispersion in the EPR line shape. This dispersion contribution previously presented in Figure 12 of ref 43 and Figures S2–S4 in the Supporting Information could be explained by the Freed et al approach 44 which is based on the stochastic Liouville equation and involves a relaxation matrix with all contributions: secular, pseudo-secular and non-secular. Mladenova et al 26 also suggested that the dispersion signal is of pseudo-secular origin; in other words, from the off-diagonal contributions to the relaxation superoperator.…”
Section: Methodsmentioning
confidence: 99%
“…The data analysis leading to the values of d⟨ B ⟩/d c and d B ex /d c has been published previously 25 and is reported in detail in the Supporting Information. The solid line is the SES equation, eq 6, assuming that r ex = r Stokes , setting f eff = 1, and assuming stick BC, Θ = 1.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have been able to separate the two effects 25 by extending the theoretical approach proposed by Salikhov. 21 …”
Section: Introductionmentioning
confidence: 99%